BUDAYA KOMUNIKASI POLITIK DI INDONESIA - Lovia Evanne; Agus Srimudin (Universitas Sumatera Selatan, 2021)
There are three kinds of political culture in Indonesian society, namely parochial political culture, subjects and participants. Parochial political culture can be seen in the lowly educated small society. They tend to be less concerned with the output that comes out of the government, which according to them does not affect their lives. Older political culture usually occurs in upper middle class society with higher levels of education and who have an interest and concern for political issues, but tend to give up because they feel they do not have the power to influence or change government policy. Meanwhile, the political culture of participants appears to be members of society who have the slightest influence in government decision making. Political elites, party elites, pressure groups or pressure groups such as NGOs, or a group of students carrying out government policies that harm the people, are examples of participant political culture.